2022
DOI: 10.3390/polym14163410
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan–Hyaluronic Acid Nanoparticles for Active Targeting in Cancer Therapy

Abstract: Cancer is the most common cause of death worldwide; therefore, there is a need to discover novel treatment modalities to combat it. One of the cancer treatments is nanoparticle technology. Currently, nanoparticles have been modified to have desirable pharmacological effects by using chemical ligands that bind with their specific receptors on the surface of malignant cells. Chemical grafting of chitosan nanoparticles with hyaluronic acid as a targeted ligand can become an attractive alternative for active targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 108 publications
1
10
0
Order By: Relevance
“…Our suggested co-delivery mechanisms of miR-375 by the fabricated NSLCs to target HepG2 cells are also aided by the CS coat. This is because our result was in line with previous studies which have suggested that cationic CS NPs possess penetration enhancer properties that allow them to have an electrostatic affinity for negatively charged cell membranes, leading to their selective accumulation in tumors, such as liver tumors by passive and active targeting [ 53 , 66 , 68 , 69 , 112 , 113 , 114 , 115 , 116 , 145 ]. Overall, as shown from our collected data, the two fabricated CS-coated NSLCs pave promising evidence to make them ideal strategies for miR-375 replacement therapy in HCC cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our suggested co-delivery mechanisms of miR-375 by the fabricated NSLCs to target HepG2 cells are also aided by the CS coat. This is because our result was in line with previous studies which have suggested that cationic CS NPs possess penetration enhancer properties that allow them to have an electrostatic affinity for negatively charged cell membranes, leading to their selective accumulation in tumors, such as liver tumors by passive and active targeting [ 53 , 66 , 68 , 69 , 112 , 113 , 114 , 115 , 116 , 145 ]. Overall, as shown from our collected data, the two fabricated CS-coated NSLCs pave promising evidence to make them ideal strategies for miR-375 replacement therapy in HCC cells.…”
Section: Discussionsupporting
confidence: 91%
“…Chitosan (CS), which is a natural and cationic polysaccharide, has been utilized by 0.5% and 1.5% to coat the surface of our NSLCs and gain benefit from its reported biocompatibility, biostability, biodegradability, target specificity [ 62 , 66 , 69 , 112 , 113 , 114 , 115 , 116 , 117 ]. Moreover, as we presented its promoted ability to form electrostatic nano-complex with miR-375 in the presence of optimized acidic pH enhance its intracellular stability as well.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-polysaccharide materials obtained with the participation of chitosan are a common practice [ 164 , 165 , 166 ]. An interesting procedure was described by Gilarska et al [ 167 ], which concerned the combination of chitosan, hyaluronic acid, and collagen for the production of an injectable hydrogel.…”
Section: Complexed Delivery Systemsmentioning
confidence: 99%
“…The in vivo therapeutic efficacy of the reported formulations was tested in the mice bearing subcutaneous-inoculated H22 tumors, and it was observed that in relation to the mice treated with POEAD-g-LA20-DOX a decrease in the tumor size was reported, reducing the growth, and demonstrating an inhibitory effect on tumoral tissue. Hyaluronic acid (HA) has been widely used in targeted drug delivery to its good biocompatibility, good water solubility, high selectivity, and aff receptors found in different tumor cells [101,102]. In order to increase the d cumulation specifically in CD44 over-expressing cancer cells, HA-attached cals and nanocarriers have been created.…”
Section: Ph-responsive Drug Delivery Systemsmentioning
confidence: 99%
“…Additionally, an internalization was observed due to the diated binding affinity of CD44 for HA with high specificity. Hyaluronic acid (HA) has been widely used in targeted drug delivery systems due to its good biocompatibility, good water solubility, high selectivity, and affinity to CD44 receptors found in different tumor cells [101,102]. In order to increase the drug/cargo accumulation specifically in CD44 over-expressing cancer cells, HA-attached pharmaceuticals and nanocarriers have been created.…”
Section: Ph-responsive Drug Delivery Systemsmentioning
confidence: 99%